KORELASI PENURUNAN MUKA TANAH DENGAN PENURUNAN MUKA AIR TANAH DI KOTA SEMARANG - Bambang Darmo Yuwono (Diponegoro University, 2013)
The characteristics of the pattern of land subsidence need to be mapped for the purposes of planning and structuring the city as well as taking appropriate actions in anticipating and mitigating the impact. These characteristics can be determined by combining the land subsidence measurements done with various methods such as levelling, GPS, direct measurement and InSAR. Land subsidence that occurred in Semarang had a rate that varied between 0 - 13 cm / year with an increasing trend towards the north east (northeast) of Semarang. The areas which had a high rate of land subsidence between 9 -13 cm / year included PRPP, Tanjungmas, Terboyo and Kaligawe. In this paper will show spatial distribution of landsubsidence which have identical pattern with the change of ground water level .Observations GPS method has a high correlation with changes in ground water level reaches 0.956 compared with InSAR observations, GPS, direct observation